Transformative learning in adulthood: A socio-contextual perspective - Karen L. Sveinunggaard (Adult Education Research Conference, 1993)
This study examined the transformative learning experiences of six adults following a self-identified critical life event. A common six phase learning process was identified which impacted six separate life spheres for each adult.